(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Hindu religious ceremonies are customs that are considered to have been inherited and continue to be carried out by the community because they believe that the existing methods are the best to be imitated and applied further. The meaci aci ceremony, which comes from a religious tradition, will be passed on to the next generation because it is part of the piodalan ceremony at the Banyuning Village Temple. Based on this, the researcher formulated the following problems, namely What is the Basic Basis for the Meaci Aci Ceremony in Banyuning Traditional Village, Buleleng District, Buleleng Regency?, What is the Form of the Meaci Aci Ceremony in Banyuning Traditional Village, Buleleng District, Buleleng Regency?. What is the Philosophical Meaning of the Meaci Aci Ceremony in Banyuning Traditional Village, Buleleng District, Buleleng Regency?. This study uses a research method to ensure that this research problem is correct, the author uses a qualitative research approach with a descriptive approach. Qualitative research aims to understand the natural phenomena experienced by the research subjects as a whole and by using various natural methods. In this study, the subjects and objects of research are described in a natural context. This study uses the Purposive Sampling technique. In addition, data collection can be done through interviews, observations, literature, documentation, and data analysis. The results of this study are the Basic Foundations of the Meaci Aci Ceremony including: Religious Foundations, Socio-Cultural Foundations, Mythological Foundations. The form of the Meaci Aci Ceremony is carried out to close negative energy in the process of picking up tirta from the Batur temple to the Banyuning traditional village temple by going through the Nunas Tirta Ceremony, Mendak, Meaci Aci, Performing Prayers, Tata Linggih Ceremony, Distribution of Tirta. The Philosophical Meaning of the Meaci Aci Ceremony includes: Religious Meaning, Ritual Meaning, Meaning of Togetherness, Meaning of Expression of Gratitude